2005
DOI: 10.1016/j.visres.2005.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Configural masking of faces: Evidence for high-level interactions in face perception

Abstract: The perception of a stimulus can be impaired when presented in the context of a masking pattern. To determine the timing and the nature of face processing, the effect of various masks on the discriminability of faces was investigated. Results reveal a strong configural effect: the magnitude of masking depends on the similarity between mask and target. Masking is absent for non-face masks (noise, houses), modest for scrambled and inverted faces and strongest for upright faces, even when they differ in size, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
42
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 48 publications
10
42
1
Order By: Relevance
“…These estimates of temporal processing capacity are not necessarily equivalent because the visual system may differ in its capacity to process a single object and multiple objects. This is evidenced by the fact that a target face is more effectively masked by another face than by a visual noise pattern (Loffler et al 2005). In general, our estimates of temporal processing capacity seem to be consistent with previous neurophysiological and neuroimaging studies of objectselective areas and provide novel evidence that high-level areas are sensitive to much lower temporal rates of visual information than early areas.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These estimates of temporal processing capacity are not necessarily equivalent because the visual system may differ in its capacity to process a single object and multiple objects. This is evidenced by the fact that a target face is more effectively masked by another face than by a visual noise pattern (Loffler et al 2005). In general, our estimates of temporal processing capacity seem to be consistent with previous neurophysiological and neuroimaging studies of objectselective areas and provide novel evidence that high-level areas are sensitive to much lower temporal rates of visual information than early areas.…”
Section: Discussionsupporting
confidence: 90%
“…People can perceive low-level motion and flicker at rates as high as 30 -50 Hz (Kelly 1961(Kelly , 1979), yet object recognition begins to decline at modest rates of ϳ8 -10 items/s (McMains and Somers 2004;Potter 1975). Recognition of a target face can be disrupted by a subsequent visual mask at much longer delays (upward of 133 ms) if the mask consists of an intact face rather than a scrambled face or visual noise (Loffler et al 2005). These results are consistent with the notion that competitive interactions between object representations occur over a more extended time period than low-level interactions.…”
Section: Discussionsupporting
confidence: 80%
“…Mask comparison for each group revealed that the upright and inverted neutral-face masks were equally effective at preventing further processing of the facial expressions, except for neutral faces presented for 50 ms. Backward masking in face identity discrimination tasks has been shown to be more effective (i.e., to yield more disruption) if the mask is configurally similar to the target (Loffler et al, 2005). In contrast, at 50 ms presentation, we found higher performance for neutral faces when an upright mask was used compared to an inverted mask.…”
Section: Discussioncontrasting
confidence: 67%
“…The temporal window over which a mask exerts its effect is thought to reflect the duration of the underlying computation. 35,36,46 If migraineurs had a processing delay, the masking functions should be shifted horizontally and the peak masking effect would be seen for longer SOAs. Such a shift clearly is not supported by the data, and the peak SOA is the same for controls and migraineurs.…”
Section: Discussionmentioning
confidence: 99%